Kasabach-Merritt syndrome with large cutaneous vascular tumors - Pavai Arunachalam; V R Ravi Kumar; Divya Swathi (Wolters Kluwer Medknow Publications, 2012)
A case series of four patients who presented with large surface vascular tumors and low platelet count and their management is reported. Medical management was done with steroids, propranolol and vincristine in different combinations. The final response was excellent without surgery.